Audiovisual Sports Media And Its Role In Developing The Sport Of People With Special Needs - Belkheir , Abdelkader; Difallah , Habiba (sports creativity, 2025)
This study came to find out the role of broadcast sports media in promoting the sport of people with special needs, specifically the sport of wheelchair basketball for the physically disabled group who practices this type of competitive sport, and by applying the descriptive and analytical method to a sample of these athletes and through a tool built from The researchers accepted specifically for this study, where the results concluded that the local sports media, which is audible, contributes ineffectively to the development of wheelchair basketball, and that broadcast media coverage is insufficient and is limited to some aspects only and does not include all aspects of this type of sport. In addition to the inferior role played by the radio in promoting sport among individuals arising from the physically handicapped